CONTINUED TEACHER TRAINING FOR AUTHORSHIP BASED ON THE TPACK MODEL AND CONSTRUCTIVE, CONTEXTUALIZED AND SIGNIFICANT APPROACH - Kanashiro, Mônia Daniela Dotta Martins [UNESP]; Junior, Klaus Schlünzen [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2021)
This study sought to analyze how elementary school teachers can use an authoring tool in practices based on the Constructionist, Contextualized and Significant approach, considering the knowledge of the TPACK model, related to the technological, pedagogical and teacher knowledge base. The action-research qualitative, started from the production of a semi-presential course applied to nine teachers. The data emerged from the observation of forums, educational materials and a self-assessment questionnaire. There was a satisfactory appropriation of the authoring tool by eight teachers; six materials created included the approach satisfactorily. Two proposals didn't include pedagogical knowledge of the TPACK model. The importance of the student's centrality in the practice planning process was evidenced and it was observed that the Constructionist, Contextualized and Significant approach has the potential to promote learning according to the TPACK model, however, he needs to consider the approach so that the integration of his knowledge is fully realized.
FORMAÇÃO CONTINUADA DE DOCENTES PARA AUTORIA BASEADA NO MODELO TPACK E NA ABORDAGEM CONSTRUCIONISTA, CONTEXTUALIZADA E SIGNIFICATIVA
Keywords: CCS approach; Early Years of Elementary School; Teacher Education; Technologies in education; TPACK